Phonological Treatment Approaches for Spoken Word Production in Aphasia - Madden, Elizabeth Brookshire; Robinson, Reva M.; Kendall, Diane L. (Seminars in Speech and Language, 2017)
This article provides an overview of phonological treatment approaches for anomia in individuals with aphasia. The role of phonology in language processing, as well as the impact of phonological impairment on communication is initially discussed. Then, traditional phonologically based treatment approaches, including phonological, orthographic, indirect, guided, and mixed cueing methods, are described. Collectively, these cueing treatment approaches aim to facilitate word retrieval by stimulating residual phonological abilities. An alternative treatment approach, phonomotor treatment, is also examined. Phonomotor treatment aims to rebuild sublexical, phonological sequence knowledge and phonological awareness as a means to strengthen lexical processing and whole-word naming. This treatment is supported by a parallel-distributed processing model of phonology and therefore promotes multimodal training of individual phonemes and phoneme sequences in an effort to enhance the neural connectivity supporting underlying phonological processing mechanisms. The article concludes with suggestions for clinical application and implementation.
Keywords: Aphasia; anomia; phonology; treatment; phonomotor